Characterization of Chlamydomonas reinhardtii phosphatidylglycerophosphate synthase in Synechocystis sp. PCC 6803 - Hung, Chun-Hsien; Endo, Kaichiro; Kobayashi, Koichi; Nakamura, Yuki; Wada, Hajime (Frontiers in Microbiology, 2015)
Phosphatidylglycerol (PG) is an indispensable phospholipid class with photosynthetic function in plants and cyanobacteria. However, its biosynthesis in eukaryotic green microalgae is poorly studied. Here, we report the isolation and characterization of two homologs (CrPGP1 and CrPGP2) of phosphatidylglycerophosphate synthase (PGPS), the rate-limiting enzyme in PG biosynthesis, in Chlamydomonas reinhardtii. Heterologous complementation of Synechocystis sp. PCC 6803 pgsA mutant by CrPGP1 and CrPGP2 rescued the PG-dependent growth phenotype, but the PG level and its fatty acid composition were not fully rescued in the complemented strains. As well, oxygen evolution activity was not fully recovered, although electron transport activity of photosystem II was restored to the wild-type level. Gene expression study of CrPGP1 and CrPGP2 in nutrient-starved C. reinhardtii showed differential response to phosphorus and nitrogen deficiency. Taken together, these results highlight the distinct and overlapping function of PGPS in cyanobacteria and eukaryotic algae.